EVALUASI KUALITAS MUTU MINYAK GORENG MENGGUNAKAN POLARISATOR TERPADU BERDASARKAN METODE FLUORESENSI ELEKTROOPTIK - heri sugito; K. Sofjan Firdausi; Nidia Kharisma Putri (Universitas PGRI Semarang, 2018)
Evaluation of quality of cooking oil using integrated polarizer based on fluorescence polarization method has been carried out. Integrated polarizer used a green laser with a wavelength of 532 ± 10 nm. Measurements were made by observing changes in fluorescence polarization angles that occurs when without an external electric field and with the provision of an external electric field produced from two copper plates given a voltage of 0-6 kV. The samples used were new cooking oil and expired cooking oil, palm cooking oil that has been contaminated by chicken oil and lard. The test results show that the change in polarization angle on cooking oil expires is greater than the new cooking oil, as well as changes in the polarization angle in palm cooking oil that has been contaminated by lard is greater than pure palm cooking oil and palm cooking oil. This indicates that the saturated fatty acid content in lard is greater than that of pure palm cooking oil and chicken oil. With these results, the fluorescence polarization method is expected to be a method for evaluating halal cooking oil.